Kontribusi Kepuasan Kerja terhadap Work Engagement pada Pekerja Generasi Z - Atthahirah, Siti; Yusra, Zulmi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the contribution of job satisfaction to work engagement among Generation Z workers. The entry of Generation Z into the workforce brings different behavioural patterns from previous generations, including a tendency to get bored quickly and a desire for constant renewal. These conditions can affect work engagement, so it is important to understand the factors that can increase work engagement, one of which is job satisfaction. This study used a quantitative method with a cross-sectional survey design and involved 100 Generation Z participants selected using accidental sampling techniques. The research instruments consisted of the 36-item Job Satisfaction Survey (JSS) to measure job satisfaction and the 9-item Utrecht Work Engagement Scale (UWES) to measure work engagement. Data analysis was performed using simple regression. The results show that job satisfaction has a positive and significant effect on work engagement (β = 0.171; p < 0.001) with an R² value of 0.541, which means that 54.1% of the variation in work engagement can be explained by job satisfaction. These findings indicate that the higher the job satisfaction, the higher the work engagement demonstrated by Generation Z workers. The results of this study can serve as a basis for organisations in designing strategies to increase job satisfaction in order to strengthen work engagement.